Solving humanity's grand challenges: Water, food, and energy - Wadhwa, Vivek (Frontiers in Research Metrics and Analytics, 2022)
Many people are fearful that the future will be one of shortages and scarcity and that because of a burgeoning population and dwindling resources, our future is grim. This couldn’t be further from reality. This is the most innovative period in human history. With several technologies on exponential and converging paths, we will be able to solve some of humanity’s grand challenges—and create an era of abundance. Imagine a world with unlimited food, water, and energy — in which we prevent disease rather than cure it and in which our lifespans increase along with our wisdom and knowledge. This is what is possible, not in future centuries, but in the next two decades.